2009
DOI: 10.1517/14728220902988549
|View full text |Cite
|
Sign up to set email alerts
|

EMP3as a candidate tumor suppressor gene for solid tumors

Abstract: EMP3 is a novel tumor suppressor gene in some kinds of malignancies, but not all, at the step of cellular immortalization rather than carcinogenesis. It may become a potent prognostic marker and a therapeutic target in such tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…We observed that this three-gene (EMP3, GSX2 and EMILIN3 ) signature can be used as a prognostic indicator for LGGs patients from both the TCGA and the CGGA datasets. EMP3 is a member of the PMP22/EMP/MP20 gene family that plays a role in cell proliferation and cell-cell interactions [27]. Previous studies reported that CpG island hypermethylation in the EMP3 promoter region is frequent in LGGs [28-30].…”
Section: Discussionmentioning
confidence: 99%
“…We observed that this three-gene (EMP3, GSX2 and EMILIN3 ) signature can be used as a prognostic indicator for LGGs patients from both the TCGA and the CGGA datasets. EMP3 is a member of the PMP22/EMP/MP20 gene family that plays a role in cell proliferation and cell-cell interactions [27]. Previous studies reported that CpG island hypermethylation in the EMP3 promoter region is frequent in LGGs [28-30].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study (22), we identified a subgroup of patients with a shorter disease-free interval and LOH 19q, a cytogenetic alteration frequently observed in OII (27,28) but not in GBM (29). We thus decided to evaluate in the same patients the methylation status of the EMP3 gene promoter located in the 19q chromosome region (19q13.3), which has gained increasing interest as it is considered a candidate tumor suppressor gene for solid tumors (15), including brain tumors. The hypermethylated status of the EMP3 gene promoter in low-grade gliomas is known as a molecular feature distinguishing them from highgrade gliomas (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…The epigenetic profiling of brain tumors has indeed significance as a prognostic index (10): e.g., the epigenetic silencing of O 6 -methylguanine methyltransferase (MGMT, 10q26) correlates with responsiveness to alkylating agents and radiotherapy in glioblastoma (GBM, WHO grade IV) (11)(12)(13). The 19q region, frequently lost in ODG tumors, harbors putative tumor suppressor genes, such as the epithelial membrane protein 3 (EMP3, 19q13.3) (14)(15)(16)(17)(18)(19). The function of EMP3 remains unclear; however, its homology to peripheral myelin protein 22 (PMP22) suggests that the protein is implicated in cell cycle regulation and cell-to-cell interactions (17).…”
Section: Introductionmentioning
confidence: 99%
“…EMP3 is expressed in most tissues, especially in peripheral blood leukocytes, ovary, intestine, and various embryonic tissues, and may regulate cell proliferation, cell-cell interactions, and apoptosis [24]. The EMP3 gene has been proposed as a candidate tumor suppressor gene on 19q13.3 in several human solid tumors, such as gliomas, neuroblastoma, pheochromocytoma, non-small cell lung cancer, and esophageal squamous cell carcinoma [59]. In these malignancies, EMP3 is frequently inactivated by a hypermethylation-mediated transcriptional gene silencing.…”
Section: Introductionmentioning
confidence: 99%